Analysis of Building-integrated Photovoltaic Systems: A Case Study of Commercial Buildings under Mediterranean Climate. (2015) - Salem, Talal; Kinab, Elias
Abstract: In the last decades, due to the significant increase in energy consumption in the building sector, many engineering strategies were developed to benefit from the use of renewable energy, particularly the solar energy. Today, building-integrated photovoltaic (BIPV) is being considered by building designers as an innovative technique for clean energy production and reduction of green house gases. Integration of PV cells in the building envelope can help in overcoming many economical and social barriers that are preventing a wider dissemination of the technology in the Mediterranean area. The BIPV components are multifunctional elements that can be used not only as energy converters, but also as shading devices, cladding, façade or roofing elements, etc. The Mediterranean countries are located in a relatively sunny area with a global horizontal radiation of 7.5–8 kWh/m 2 in summer. However, the temperature in these countries can reach high levels for the same period. This can affect the performance of the BIPV cells. In this paper, BIPV systems are analyzed through a literature review where the BIPV systems that are most suitable for Mediterranean climate are investigated according to architectural constraints. The case of commercial buildings is considered where different integration scenarios are compared and analyzed. The energy performance of BIPV systems is assessed through modeling and simulations by a simplified approach taking into account various parameters such as the climate, tilt angle, azimuth angle, and types of cells. Prospects for the development of this sector are discussed at the end of this paper.